(untitled) (Journal of the College of Education for Women, 2019)
This research deals with a problem of a large degree of importance. As globalizationhas caused the emergence of global market for education. And it began the spread ofinformation technology leaves its impact on the attainment within the school in more thanfield.Therefore, it is necessary to find effective educational leadership could keep up withdevelopments in the field of education. Therefore this research interested in recognition thefoundations of effective educational leadership in terms of functions, and the preparation ofeducational leaders. Accordingly, research has included three chapters, the first chapterdiscusses the general frame work of the study contains the problem of the research, itsimportance, objectives and the most important concepts. The second chapter is devoted toeducational leader ship- tasks and styles. The third chapter was the the theories of educationalleader ship, and preparing leaders. In conclusion, the results and recommendations andsuggestions.